Ecological Features and Distribution of Scenic Liana Species (Eurasian Research Bulletin, 2024)
The article about in detail the botanical characteristics of lianas and their occurrence in nature. The scientific literature also describes the characteristics of lianas as an ornamental plant species and their adaptability to nature. The distribution of ornamental liana species in the countries of the world has been scientifically analyzed in terms of its adaptability, beneficial properties for humans and nature. The article also discusses the types of lianas found in Uzbekistan and their decorative features.